Cross-linked starch-based edible coating reinforced by starch nanocrystals and its preservation effect on graded Huangguan pears. (1st May 2020) - Dai, Limin; Zhang, Jun; Cheng, Fang
Highlights: Cross-linked cassava starch-based coating reinforced by SNCs has been prepared. Film/coating with 6% SNCs has the best comprehensive performance. The coating has a significant effect on the preservation of Huangguan pear. The effects of the order of coating and grading treatment have been studied. The results can assist in the preparation of starch-based coating on fruits. Abstract: Starch-based nanocomposite film/coating made from cross-linked cassava starch reinforced by starch nanocrystals (SNCs) was successfully prepared. The effects of SNCs contents on the color, transparency, roughness, mechanical properties, water vapor permeability, and FTIR spectroscopy of the films were explored. The results showed that the film with 6% SNCs had the best comprehensive performance. Subsequently, graded Huangguan pears were coated with the formulation-optimized coating and stored at 20 °C for 4 weeks. From the physicochemical parameters of pears, it can be found that the grading treatment was detrimental to the preservation of pears, while the coating treatment was significantly effective for extending shelf life. Besides, the pattern of grading before coating was more advantageous for pear preservation. In general, this study firstly applied cross-linked starch-based nanocomposite coating on the preservation of pear, which had practical significance for expanding the use of nanocomposite coating reinforced by SNCs and pear preservation methods.